2016
DOI: 10.1111/febs.13669
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin‐1‐dependent activation of the metalloprotease TACE/ADAM17 by TGF‐β in hepatocytes requires activation of Src and the NADPH oxidase NOX1

Abstract: Transforming growth factor-b (TGF-b) plays a dual role in hepatocytes, inducing both pro-and anti-apoptotic responses, the balance between which decides cell fate. Survival signals are mediated by the epidermal growth factor receptor (EGFR) pathway, which is activated by TGF-b. We have previously shown that caveolin-1 (CAV1) is required for activation of the metalloprotease tumour necrosis factor (TNF)-a-converting enzyme/a disintegrin and metalloproteinase 17 (TACE/ADAM17), and hence transactivation of the EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…ADAM17 has been described to be associated with lipid rafts 35 and especially with caveolin-rich membrane domains 36 37 . Since PMA-induced internalisation of ADAM17 is not solely clathrin dependent, we investigated whether inhibition of caveolin-dependent internalisation by genistein influences the cell-surface expression of ADAM17.…”
Section: Resultsmentioning
confidence: 99%
“…ADAM17 has been described to be associated with lipid rafts 35 and especially with caveolin-rich membrane domains 36 37 . Since PMA-induced internalisation of ADAM17 is not solely clathrin dependent, we investigated whether inhibition of caveolin-dependent internalisation by genistein influences the cell-surface expression of ADAM17.…”
Section: Resultsmentioning
confidence: 99%
“…This encouraging result that, surprisingly, had not been explored before, pushed us to analyse the relevance of clathrin expression in the response of an immortalized cell line of mouse hepatocytes and an HCC cell line, PLC/PRF/5, both of them used in our previous studies to analyse EGFR and TGF-b signalling. 14,15,18 According to our data, clathrin is essential for the hepatocyte and liver tumour cell response to EGFR ligands, such as HB-EGF, in terms of full EGFR/Akt/ERKs phosphorylation and cell proliferation ( Fig. 2 and Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Once cells overcome apoptosis, they respond to TGF-b by undergoing epithelialmesenchymal transition (EMT), which confers migratory/invasive capacities and stem cell properties. 16 We have recently reported that caveolin-1, a protein involved in intracellular traffic for which a role in HCC has been proposed, 17 is necessary for the TGF-b-induced transactivation of the EGFR, 18 switching the response to TGF-b from cytostatic to tumorigenic in liver tumour cells. 19 Much less is known about the potential role of clathrin in the TGF-b signalling in liver cells.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β-mediated activation of NOX1 promotes autocrine growth of liver tumor cells through the activation of the EGFR pathway, via upregulation of EGFR ligands expression through a c-Src ( 151 ) and NF-κB ( 152 ) dependent mechanism. The autocrine loop of EGFR activated by TGF-β in non-transformed hepatocytes and liver cancer cells requires the activity of the metalloprotease TACE/ADAM17 ( 142 , 146 ) in a Caveolin-1/Src/NOX1 dependent manner ( 153 , 154 ). This proliferation can be impaired by the addition of the NOX inhibitor VAS2870 ( 155 ).…”
Section: Role Of Tgf-β During Hepatocarcinogenesismentioning
confidence: 99%